Analisis Faktor Penyebab Kesulitan Belajar Siswa pada Pembelajaran Biologi Kelas XI SMA Negeri 2 Tondano Tahun Ajaran 2024/2025 - Muliati Muliati; Herry M. Sumampouw; Christny F.E. Rompas (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
The aim of this study is to identify the factors that cause learning difficulties among students in biology lessons in class XI at SMA Negeri 2 Tondano during the 2024/2025 academic year. The identified issues include students having difficulty understanding the material taught, lacking focus during lessons, ineffective teaching strategies, and low student motivation. This research uses a descriptive approach with a qualitative design, where data was collected through interviews and documentation. The study was conducted from November 6 to November 28, 2024, with 18 class XI students as the subjects. Interviews were conducted using 100 prepared questions. Data analysis was performed descriptively with percentage calculations. The results indicate that internal and external factors influence the factors causing learning difficulties in biology lessons for class XI students. Internal factors include interest (26.5%), motivation (35.9%), physical health (38.3%), intellectual ability (28.6%), attitude (43.4%), learning attention (32.3%), learning readiness (48.9%), talent (42.5%), physical condition (25.3%), and emotional factors (32.5%), all of which are categorized as low. External factors include family environment (48.9%), school environment (45.6%), interaction with teachers (42.7%), interaction with peers (35.4%), facilities and infrastructure (54.6%), technology and learning media (63.6%), curriculum (65.4%), learning environment at home (52.3%), family economic conditions (56.7%), and school education policies (43.5%), with most of these external factors showing a low to moderate category. This study concludes that class XI students at SMA Negeri 2 Tondano experience the most significant learning difficulties related to external factors, such as the curriculum, and internal factors, such as students' learning readiness.